Purslane (Portulaca oleracea) Ethanol Extract decreases hs-CRP levels and Total Score of Renal Tubular Degeneration in Rat Model of Gentamicine-Induced Renal Damage - Saptaningtyas, Ragil; Chasani, Shofa; Nasihun, Taufiqurrachman (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2020)
Introduction: Injection of intraperitoneal gentamicin at a dose of 60 mg/kg BW intra-peritoneal in rats for 7 days has been shown to trigger renal tubular degeneration and increase in high sensitivity C-reactive protein (hs-CRP) level. The use of purslane (Portulaca oleracea) to reduce hs-CRP levels and total score of renal tubular degeneration has not been reported.Objective: to determine the effect of purslane ethanol extract on hs-CRP levels and renal tubular degeneration score in gentamicin induced-renal damage in rats.Methods: This was a study using posttest only control group design. Twentyfive male Wistar rats aged 8-12 weeks, weighed 150-200 grams were allocated into 5 groups: normal (Nor-G), without treatment; negative (Neg-G), gentamicin (60 mg/kg BW), intraperitoneally; P-200; P-300 ; P-400 (gentamicin plus purslane extract at a dose of 200, 300, and 400 respectively) for 7 days. The hs-CRP was evaluated using the ELISA method. Total score of renal tubular degeneration was evaluated using modified score of Sarjadi.Results: there was a significant difference in mean hsCRP level and total score of renal tubular degeneration between groups (p <0.05). Posthoc analysis showed that hsCRP level and total score group of P-200, P-300 and P-400 were significantly lower than those of Neg-G, p <0.05. Meanwhile, the levels of hsCRP and total score of renal tubular degeneration in P-200, P-300, P-400, and Nor-G groups were not significantly different (p> 0.05).Conclusion: the administration of purslane ethanol extract at doses of 200, 300, and 400 mg/kg BW for 7 days improve hs-CRP level and total score of tubular degeneration similar to normal.Â